2018
DOI: 10.1038/s41598-018-33037-2
|View full text |Cite
|
Sign up to set email alerts
|

Impaired tumor growth and angiogenesis in mice heterozygous for Vegfr2 (Flk1)

Abstract: VEGF signaling through its tyrosine kinase receptor, VEGFR2 (FLK1), is critical for tumor angiogenesis. Previous studies have identified a critical gene dosage effect of VegfA in embryonic development and vessel homeostasis, neovascularization, and tumor growth, and potent inhibitors of VEGFR2 have been used to treat a variety of cancers. Inhibition of FGFR signaling has also been considered as an antiangiogenic approach to treat a variety of cancers. Inhibition of VEGFR2 with neutralizing antibodies or with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Tumour neoangiogensis requires VEGF, which is secreted in the tumour microenvironment. VEGF‐A activates VEGFR2 on nearby ECs to induce their sprouting into the tumour . VEGF‐independent angiogenesis has also been described .…”
Section: Resultsmentioning
confidence: 99%
“…Tumour neoangiogensis requires VEGF, which is secreted in the tumour microenvironment. VEGF‐A activates VEGFR2 on nearby ECs to induce their sprouting into the tumour . VEGF‐independent angiogenesis has also been described .…”
Section: Resultsmentioning
confidence: 99%
“…Monocyte-derived phagocytes (alveolar macrophages and dendritic cells) are present in the lung throughout alveologenesis and contain lineage-labeled particles from alveolar myofibroblasts at least through postnatal day 31, suggesting a role in removal of dead alveolar myofibroblasts through a phagocytic process. (Oladipupo et al, 2018), rabbit anti-NG2 (1:200, MilliporeSigma; ab5320) (Kato et al, 2018), rat anti-CD68 (1:200, Bio-Rad, MCA1957) (Menon and Fisher, 2015), rat anti-F4/80 (1:100, Bio-Rad, MCA497R) (Hasan et al, 2013) and rabbit anti-Desmin (1:100, Abcam, ab8592) (Walton et al, 2016).…”
Section: Antibodiesmentioning
confidence: 99%
“…VEGF signaling via tyrosine kinase receptor VEGF receptor 2 (Flk-1) has a critical role in tumor angiogenesis and promotion of VM in cancer (71,72). Blood vessels detected in the VM of glioblastoma cells are integrated by mural cell-lined vasculature.…”
Section: Mechanisms Of Vm In Human Cancersmentioning
confidence: 99%
“…Also, low miR-200a expression has been associated with tumor grade and metastasis (88). VEGF expression has been detected in hypoxic environments, and its secretion by tumor cells plays a crucial role in the tumor angiogenesis and VM formation (71,72). Salinas-Vera et al reported that miR-765 decreased VEGF expression after hypoxic conditions in ovarian cancer.…”
Section: Regulation Of Vm By Mirnas In Solid Tumorsmentioning
confidence: 99%